Tax changes in the EU-13 during the recent financial crisis - Nika Šimurina; Dajana Barbić (International Entrepreneurship Review, 2017)
The aim of this paper is to identify tax changes during the recent financial crisis across EU-13 member states. The recent financial and fiscal crises have changed taxation trends in a large number of EU member states. The member states have been hit differently by the crisis depending mostly on the different degree of macroeconomic imbalances in the economy. Therefore policy responses varied among them and were strongly connected with macroeconomic and fiscal conditions. The tax systems in the EU-13 are transparent, neutral, and straightforward, though not necessarily efficient. In terms of the tax structure, most EU-15 member states raise roughly equal shares of tax revenues from direct taxes, indirect taxes, and social contributions, while the EU-13 member states often display a substantially lower share of direct taxes in total tax revenues. The paper includes theoretical background, comparison of present differences among the taxation systems of the EU-13 member states, and advantages and disadvantages of different types of taxes.